ABORSI TERHADAP KORBAN TINDAK PIDANA PEMERKOSAAN - SH., MH, Novita Novi (Belom Bahadat, 2023)
The act of abortion is actually prohibited by law, but based on Law Number 36 of 2009 concerning Health in Article 75 paragraph 2 there are exceptions. It is permissible for an abortion to be carried out if it fulfills several provisions which have become the main basis that cannot be violated, both in the Criminal Code and special rules that have been set by the government. Abortion is justified according to the provisions of the rule of law because it is to save one's health or life. The Criminal Code clearly stipulates abortion as a crime, but this provision can be overridden by the provision of abortion exceptions in the Law on Health. Like the prohibition on abortion regulated in the Criminal Code, basically the Law on Health also prohibits abortion. The formal law governing the issue of abortion states that the Indonesian government rejects abortion. Exceptions are given if there are medical indications as stated in the Law on Health. In addition, the issue of abortion is also related to the oath of Indonesian doctors, which among other things states that doctors will respect every life. The fundamental problem in the world of health is whether there are medical reasons that justify it, so that when a medical procedure is carried out with reasons justified by law, the act of abortion is not categorized as a crime or crime. Unlike the case when the act of aborting a pregnancy is carried out without any justifying medical reasons, namely reasons for the sake of human dignity, such as covering shame and so on, then such actions can be included in the formulation of unlawful behavior including criminal acts of abortion. Keywords: Abortion, Abortion Exception, Rape Victims